Adiwiyata as an Effective Environmental Education Program: How to Create and Maintain It? - Rista Anggraini; Sugeng Utaya; I Nyoman Ruja (Universitas Veteran Bangun Nusantara, 2024)
Environmental education is important to preserve, one of which is through the Adiwiyata program. The reality in the field is that implementing the Adiwiyata program is not easy, strategies are needed to preserve and overcome existing problems. This research aims to describe the strategy for implementing the Adiwiyata program, and the efforts made by schools to preserve the environment. The method used is descriptive qualitative. The data collection techniques used were interviews, observation, documentation, and literature study. The results of this research are that to implement the Adiwiyata program some steps are continuously being taken (1) creating environmentally friendly policies, (2) environmentally based curriculum, integrated through subjects and extra-school, (3) participatory based environmental activities, carried out through familiarization and creation School Policy Letter, and (4) management of environmentally friendly supporting facilities. Students' environmentally caring character can be formed through habits. Efforts made to preserve the environment include making habits, utilizing plastic waste, and making picket schedules for caring for plants. In essence, environmental education is an important milestone in forming a character who cares about the environment. Therefore, this research has an important role as a reference in developing environmentally caring character in students.